Foetal Position Monitoring and VR Workouts - Dr.Jeya Daisy I; Sobika M; Afila B; Barath Kumar E (International Journal of Medical Toxicology and Legal Medicine, 2025)
A serious condition during pregnancy, fetal malposition can lead to issues such as delayed labor, increased discomfort for the mother, and a higher rate of Caesarean section. This study presents a novel, integrated method for tracking fetal position in real time that combines gyroscopes and accelerometers with inertial measurement units (IMUs). Advanced algorithms are used by the system to process continuous movement data, identify fetal postures that are not optimal, and instantly notify pregnant women and medical professionals. Furthermore, a workout program based on virtual reality (VR) is incorporated to facilitate fetal relocation through supervised physical activities. In order to reduce the risks of malposition and improve maternal health outcomes and the possibility of a natural, straightforward birth, the technology combines interactive VR-augmented exercises with real-time fetal position surveillance.